Improving America’s Communities Policy Proposals that Increase Civic Engagement and Improve America’s Built Environment (Hinckley Journal of Politics, 2017)
Recently, America has begun to experience significant declines in civic engagement. At the same time, nearly half of all Americans are currently living in suburban communities that are fraught with challenges ranging from a lack of community institutions, traffic congestion, isolation, pollution and high levels of land consumption. This paper explores the hypothesis that improved urban planning, new tax structures, and more effective municipal government participation in planning will enable communities to develop in a way that will increase civic engagement among their residents while reducing the damaging effects of poorly planned suburban sprawl.